Estudio de pre - factibilidad para la instalación de un café-sanguchería, con proyección a una franquicia en Lima Metropolitana - Méndez Pérez, Jorge Luis (2017)
The present study searches to implement a coffee-sangucheria (AYRA), in which will be offered sandwiches, salads, coffees, juices and other products that can satisfy the need of feeding of an urban population, which has great appreciation for the high quality and the short time of service. According to the market study that has been realized, the target audience are defined by people between 18 and 49 years old, belonging to socioeconomic levels A and B, residents of modern Lima, it is estimated that in the year 2020 58 765 people will be attended, which infers that 161 customers will be served daily that year. For the following measurements it is considered that each client will consume a combo menu, which consists of a chicken sandwich and a coffee. The coffeeshop will be located on Avenida Larco, that is located in the district of Miraflores, this was determined after analyzing the qualitative aspects offered by different locations, choosing the one that offers greater possibilities of success for the project, due to its proximity to the target market, location, ease access and public affluence. The installed capacity of service either by technology and size exceeds the size of the market, this being the only limitation. The kitchen will have semiautomatic technology, which is easy to operate and will be used by technically qualified personnel. We will seek to offer the best quality in products as well as in service, not only because the target market demands high standards, but also because we consider that maintaining a high level of quality is a key success factor, to ensure this, BPM systems will be implemented. and HACCP in addition to working with suppliers that have the same systems. The amount needed to develop the next project is S / 186 065 soles, which consists of an own investment (40%) and a financed amount (60%). According to the economic and financial analysis carried out, a positive viability of the project can be determined, because a COK are greater than the TEA of the financial loan, a financial NPV of S/154 722 soles, an IRR of 85%, a recovery period of 1,19 years and finally a Benefit rate / cost of 3,10.